(untitled) (International Journal of Food and Nutritional Sciences, 2022)
1969 saw the introduction of the National Service Scheme by the Indian government. The programme encompasses a wide range of activities and aims to foster the holistic development of young individuals by engaging them in voluntary services. This report focuses on the evolution of N.S.S. in different colleges within the current state of Manipur. This endeavor also entails a re-examination of the aims and extents of the National Service Scheme (N.S.S.). This paper aims to clarify the significance of youth-led events that foster responsible citizenship in the long run.